C677T and A1298C MTHFR gene polymorphisms and response to fluoropyrimidine-based chemotherapy in Mestizo patients with metastatic colorectal cancer - Ramos Esquivel, Allan Eduardo (2021)
Objective: To assess the association between C677T and A1298C methylenetetrahydrofolate reductase (MTHFR) single-nucleotide polymorphisms (SNPs) and response to first-line fluoropyrimidine-based chemotherapy for metastatic colorectal adenocarcinoma. Methods: A total of 68 patients were prospectively followed up in San Juan de Dios Hospital (San José, Costa Rica) from January 2019 to November 2020. Patients received first-line therapy with capecitabine or 5-fluorouracil in combination with oxaliplatin or irinotecan. Germline and somatic DNA was extracted from blood samples and paraffin-embedded tissue, respectively. Overall response rate (partial response + complete response) was assessed according to RECIST 1.1 criteria. Cox regression models were performed to identify the effect of MTHFR C677T and A1298C SNPs on progression-free survival (PFS) and overall survival (OS) (NCT registration number: 03852290). Results: Patients harboring one or both T alleles of the MTHFR C677T SNP had better overall response than homozygous wild-type individuals [odds ratio (OR): 3.21; 95% confidence interval (CI), 1.05–9.81; P = 0.03]. No association was found between the MTHFR A1298C genotypes and overall response (OR: 0.75; 95% CI, 0.26–2.20; P = 0.60). Patients with the MTHFR 677 TT and CT genotypes had longer PFS than CC individuals (hazard ratio: 0.53; 95% CI, 0.28–0.98; P = 0.045), even after adjustment for confounders (hazard ratio: 0.50; 95% CI, 0.25–0.98; P = 0.04). We found no association between the MTHFR A1298C SNP and PFS (hazard ratio: 1.35; 95% CI, 0.72–2.55; P = 0.34). None of the SNPs was associated with OS. Conclusion: Patients carrying at least one mutant allele of the MTHFR C677T SNP had a better overall response and longer PFS than wild-type homozygous patients.